Innovations at the Human-Computer Interface: A Medical-Informatics Perspective - Horvitz, Eric (Proceedings of the First Conference on Medicine Meets Virtual Reality, San Diego, California, June 1992., 1992)
Research on computer-based decision support in medical informatics has been concerned largely with the development of representation and inference methodologies, and the delivery of reasoning techniques on traditional computing platforms. Nevertheless, there has been growing attention to the development of more powerful and elegant human-computer interfaces, with new interaction modalities, including the use of perspective-following simulation and telepresence. I shall describe several promising directions and opportunities surrounding the human-computer interface in computer-based medical systems. I shall first discuss the form of decision support that might someday be accessed regularly during the practice of medicine. Then, I will describe the utility-directed display of information, intelligent user-modeling, and information sharing. Finally, I will present several new platforms and functionalities that I see playing a significant role in the near future. These include a set of techniques allowing hands-free interaction, methods for overlaying or keying information to anatomic structures during surgery, and micropresence–a technique that allows physicians to effectively enter and perform microsurgery in small areas of a patient's anatomy.